PARADIGMA TRAUMA CATHY CARUTH DALAM PUISI MEDITASI ABDUL HADI WIDJI MUTHARI - Zainaldy, Mochammad Bagja Agung Nugraha; Jihadah, Nurlaila (Universitas Padjadjaran, 2026)
ABSTRACT. This analysis interprets Abdul Hadi W.M.’s poem “Meditasi” through Cathy Caruth’s trauma framework, emphasizing the influence of latency and deferred awareness on the subject’s religious turmoil. The approach utilized is a meticulous analysis of “Meditasi” to examine diction, corporeal imagery, ritualistic repetition, transitions between sacred regions, and alterations in the stance of the lyrical “Aku” The results indicate that the sacred experience is simultaneously captivating and detrimental: physical chill, the fatigue of traversing hallowed sites, and the incessant knocking from door to door signify the resurgence of an experience that never achieves a cohesive comprehension. Repetitions of devotion are interpreted as indicators of intrusive memory, but the desert picture highlights a survival mechanism when doctrine fails to offer guidance. The political aspect culminates when God is shown as possessing an increasingly restricted sense of nationality, making universalism a contentious arena of representation. The concluding aporia, expressed through a sequence of inquiries regarding God’s name, origin, ethnicity, and religion, serves as an ethical rejection of sacred possession. This study introduces the notion of traumatized spirituality to elucidate how the poetry embraces wounds without resolving them through theological certitude. Its significance is in delineating the connection between trauma, Sufism, and religious nationalism in contemporary Indonesian poetry, while illustrating that Caruth’s paradigm may be contextualized within local texts without diminishing the cultural contexts being examined.